RARE EARTH ELEMENTS ENRICHMENT OF FIXED-BED COAL ASH FROM A PILOT PLANT GASIFICATION BY PHYSICAL METHODS - Suganal Suganal (Puslitbang tekMIRA, 2018)
Research and development regarding coal gasification at a pilot scale in Palimanan has been conducted since 2008. Besides the gas product, attention on chemical element identification within the bottom ash is also necessary. The aim is to implement the research and development activities in integrating coal utilization processes by zero waste. The most important content within the coal ash is the precious metal elements, namely the rare earth elements. Characterization on the fixed bed gasification coal ash from Palimanan pilot plant shows that the ash contains the rare earth elements (REE) such as cerium, lanthanum, samarium, neodymium, praseodymium, euporium, gadolinium, dysprosium, and yttrium. Its bearing minerals include zircon silicate minerals (ZrSiO4) and monazite-Ce (CePO4). The total content of the rare earth elements is 77.85 ppm. In this work, the rare earth elements concentration successfully increased using shaking table and magnetic separator methods. It reached up to 217 ppm. However, the shaking table was more effective to increase the concentration. Approximately two times concentrates were achieved, while no significant results derived from the magnetic separator process.